Characterizing the hippocampal theta’s response to carbachol; using a complete septo-hippocampal preparation - García Méndez, K. M.; Macías, M.; González Pereyra, P.; Salas Gallardo, A.; Williams, S.; Peña Ortega, F.; Mondragón Rodríguez, S. (Revista Mexicana de Ingenieria Biomedica, 2017)
The present study describes the pharmacological analysis of the effects of carbachol, a cholinergic agonist, on hippocampal theta activity. Knowing that this activity is critically related to cognitive function and altered in patients with neurodegeneration, pharmacological efforts aiming to directly modulate hippocampal theta activity becomes of central importance. In a recently developed complete septo-hippocampal preparation, carbachol elicited significant theta power enhancement with 1 μM. Concentrations under 1 μM and over 2 μM carbachol caused significant reduction in the power of hippocampal theta activity. Carbachol effects were completely blocked with the cholinergic antagonist scopolamine. At the experimental level, it is the first time the direct action of a cholinergic agonist is evaluated in the septo-hippocampal pathway completely isolated. However, carbachol as a cholinergic agonist is a drug with a certain level of nonspecific response. That is why to correct this experimental limitation, we used scopolamine (cholinergic antagonist) which allowed us to corroborate the effects on the cholinergic pathway. In summary, electrophysiological assays demonstrated an effective concentration range of carbachol specifically modulating hippocampal theta activity.